2007
DOI: 10.1007/s10815-007-9106-0
|View full text |Cite
|
Sign up to set email alerts
|

The utility of serum leptin and follicular fluid leptin, estradiol, and progesterone levels during an in vitro fertilization cycle

Abstract: Purpose: To prospectively evaluate serum and follicular fluid leptin, estradiol, and progesterone levels during in vitro fertilization.Methods: Prospective observational study measuring serum levels at six points during the IVF cycle and follicular fluid at the time of retrieval.Results: Serum leptin and estradiol levels both significantly increased for the individual patients during the IVF stimulation process. None of the leptin levels differed based on pregnancy outcome. BMI significantly correlated with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 19 publications
5
26
0
Order By: Relevance
“…In bovine oocytes high concentrations of leptin decreased cleavage rates and development to blastocyst stage, but did not affect gene expression [57]. In women, elevated leptin is associated with higher BMI [58], and in vitro studies of human granulosa cells indicate leptin can impair steroidogenesis [59]. Lower intrafollicular leptin does not differ between PCOS and control women, but is associated with higher BMI.…”
Section: Oocyte Maturation and Fertilizationmentioning
confidence: 94%
“…In bovine oocytes high concentrations of leptin decreased cleavage rates and development to blastocyst stage, but did not affect gene expression [57]. In women, elevated leptin is associated with higher BMI [58], and in vitro studies of human granulosa cells indicate leptin can impair steroidogenesis [59]. Lower intrafollicular leptin does not differ between PCOS and control women, but is associated with higher BMI.…”
Section: Oocyte Maturation and Fertilizationmentioning
confidence: 94%
“…Various reasons such as mild defects in spermiogram, slight hormonal changes and underlying pathophysiological mechanisms are involved in unexplained infertility [3]. Leptin is a hormonal factor affecting ovulation and the ovary through both paracrine and endocrine actions [4]. It also plays a key role in energy homeostasis and body weight regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is also produced by the ovary, and estradiol has a stimulatory effect on its production. In low concentrations, leptin has stimulatory effects, and in high concentrations, it has inhibitory effects on gonadotropins [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we did not measure the E 2 levels in follicular fluid. It has been reported that E 2 levels in the serum were positively correlated with the E 2 levels in follicular fluid [25,26]. It is therefore unlikely that there is a considerable discrepancy in E 2 levels between the serum and follicular fluid.…”
Section: Discussionmentioning
confidence: 94%